La planeación curricular en las prácticas docentes (Memorias Sifored - Encuentros Educación UAN, 2023)
This presentation it is discusses the importance of planning in relation to good teaching practices, and how it affects the innovation of educational practices, as well as learning and the effectiveness of the teaching process from a qualitative-reflexive approach with the objective of to identify how planning benefits the educational and practical process of the teacher. Which allowed to reach the conclusion that planning allows teachers optimal preparation and awareness when training, where planning aims to generate innovative teaching strategies to the needs of students. It is concluded that prior preparation of a lesson provides a number of significant advantages for both teachers and students. By investing time and effort in carefully planning the content, structure, and resources of a lesson, a more effective and enriching learning experience is achieved. Key benefits of preparation include increased organization, clearer communication, time savings, improved quality of material, adaptation to student needs, teacher motivation and confidence, effective assessment, controlled flexibility and more useful feedback. Ultimately, pre-preparation contributes to a more productive and successful learning environment, where both teachers and students can achieve their educational goals more effectively.
Keywords: Planning; innovation; educational practices; Teaching